Wet and Dry Periods in Regions Surrounding the Atlantic Ocean Basin - Silvina A. Solman (Frontiers Research Topics, 2016)
The Atlantic Ocean is the second largest of the world's oceanic divisions. It is bounded by the continents of America, Europe and Africa and at its polewards margins by the Arctic and the Southern Oceans. Different climatic patterns can be observed along its large latitudinal domain, which extends from the equator to sub-polar regions. Thus, different tropical and extra-tropical meteorological systems may have some influence on the characterization of precipitation regimes observed surrounding the basin, such as the Intertropical Convergence Zone (ITCZ), tropical monsoon systems, westerly storm tracks and atmospheric rivers. The subtropical regions of the Azores and South Atlantic high pressure systems are large evaporative areas which act as important moisture sources for the adjacent continents. Variations in the oceanic characteristics may influence the moisture transport towards the neighboring landmasses and alter the precipitation. The influence of climatic variability modes manifest not only over the Atlantic Ocean, but also over other oceanic regions, may also interact with the regional hydrological budget, thereby generating long periods of drought or excessive precipitation over the Atlantic rim landmasses. This Research Topic intends to highlight the advances of the scientific community in investigating the continental precipitation surrounding the Atlantic Ocean and its variability on various temporal and spatial scales.